The dark side of the work of immigrant women caregivers in Spain: Qualitative interview findings - Jesús Rivera‐Navarro; Alberto Del Rey; Tania Paniagua (Wiley, 2019)
Abstract Aim To analyse the perception that immigrant women caregivers have of their relationship with the person receiving the care and their family and the possible impact those relationships may have on a caregiver's health. Design A qualitative study was conducted. Methods Thirty‐four semi‐structured interviews were applied in the Spanish city of Salamanca from November 2015-November 2016. The "interpretative hermeneutics" technique was used as the framework for the analysis. Results The discourse studied indicated that the immigrant women's cultural background, as well as their gender's assumed stereotypes, gave rise to an emotional attachment to the person receiving the care, which could generate a burden. Most of the women interviewed reported situations of abuse from the old people under their care. The fact that increasingly more old people are being cared for by immigrant women renders it necessary for social and health policies to consider this collective.